Penanganan Terhadap Anak Korban Kekerasan Seksual Yang Dilakukan Oleh Keluarga Terdekat - Timisela, Victor Riko Febrianko; Sopacua, Margie Gladies; Fadillah, Astuti Nur (Faculty of Law Universitas Pattimura, 2025)
Sexual violence against children has long-term impacts and reflects systemic failures in protection, especially when perpetrators are family members. Despite existing regulations, cases continue to rise, and victims often remain silent due to social pressure. This study is needed to understand the root causes and develop more effective prevention strategies. The results show that in terms of handling efforts by means of a curative approach, efforts made by related institutions include psychological assistance and rehabilitation, legal services and advocacy, medical care and health recovery, temporary shelters, and social reintegration and family support.